Parentesen i verdenshistorien – krisen vi aldrig har forstået - Steen, Jens Jonatan (Politik, 2012)
European welfare states face great challenges these years. Particular attention is drawn to the economic and scal troubles, but the key threats to continued welfare can also be found in the weakening of the welfare states foundational institutions. roughout the last three decades, unions, public schools, public housing, public hospitals and other insti- tutions constructed to satisfy collective needs have experience less support and less popularity. e political responses to the nancial and economic crisis does only exaggerate these troubles caused by these tendencies. Fierce austerity policies are imposed and justi ed on the basis of a false claim that government budget de cits are caused by excessive welfare spendings. Where actually, the de cits are the direct result of governments and populations carrying the burden of debt created in the private nancial sector. At the same time, the global nancial sector still disappoints immensely. e sector may excel in the creation of questionable assets with large ctitious monetary value attached to them, but fail to contribute to strengthening the real productive parts of the economy, real job creation and real value creation. Center-left political powers in several European states are increasingly defending the needs of their popula- tions as well as realizing that the frenzy nancial sector has been left unregulated for too long and that things has to change. But their power is constrained decisively by both powerful international institutions guided by neoliberal economic theory and the pro t-demands of global markets investors.